The Contemporary Use of Riddles: Riddles in Fiction and Theatre (Based on the Example of Rimantas Kmita) - Kensminienė, Aelita (Tautosakos darbai, 2026)
This article examines the contemporary use of riddles in creative professional works, such as fiction and theatre. The works of the popular contemporary Lithuanian writer Rimantas Kmita contain many riddles, and so as he offers an exceptional illustration of this phenomenon he was chosen as the basis for the analysis. The following three works were selected: the novel Remyga (2020), the play of the same name (premiere 2020, dir. Oskaras Koršunovas), and the comic book Keliuonė. Įmink Šiaulius (2023) by Kmita and the artist Povilas Vincentas Jankūnas. Translated literary works and plays by foreign authors are used in the article to provide a cultural context for the use of riddles in authorial work. These include children’s and popular literature, as well as classical dramatic works containing riddles and which have influenced the use of riddles, such as Lewis Carroll’s Alice’s Adventures in Wonderland and Through the Looking-Glass, and What Alice Found There, J. R. R. Tolkien’s The Hobbit, or There and Back Again, Sophocles’ Oedipus the King, and Giacomo Puccini’s “Turandot”. Kmita’s work is viewed as a case study, although from a narrow perspective, i.e. in considering what riddles the author uses and what they add to the work.
Keywords: riddles; the riddle of the Sphinx; novel; comic book; theatre